A clustering algorithm to evaluate the attitude of Brazilian researchers regarding open access research data - Freitas, Bruna S.; Bottero, Diego; Lucca, Giancarlo; Borges, Eduardo N.; Santos, Helida; Dimuro, Graçaliz P. (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC); 2021: Anais do XVIII Encontro Nacional de Inteligência Artificial e ComputacionalDO - 10.5753/eniac.2021.18290, 2021)
The core point of the research process are data. They are records from scientific investigation, which support the results published in journals and conferences. Making research data available in open access digital repositories has many advantages, such as increasing the visibility of associated publications, reproducing experiments, and validating results. In Brazil, full and unrestricted sharing of them is not yet accepted by most researchers. This paper presents an initial study to describe a model analyzing the attitude of Brazilian researchers concerning open access research data. A clustering algorithm was used to identify different research profiles. The achieved results indicate the main reasons why the researchers object to share their data.